Risk and safe practice pattern for ophthalmologists in seropositives (Panacea Journal of Medical Sciences, 2020)
Objective: To analyze the risk involved in eye surgery and follow safe practice pattern in Seropositive [Hepatitis B (HBV), Hepatitis C(HCV) and Human Immuno-deficiency Virus (HIV)] cases.Materials and Methods: This retrospective analysis was done at a Private Eye Hospital in Tier three city of Haryana, North India. Duration of study was from 1.4.2015 to 31.3.2020. Total of 1803 patients’ data was screened and analyzed. All patients who  underwent eye surgery in our hospital and viral markers testing was done were included in the study.Results: Out of 1803 patients’ data screened, 62 (3.44%) patients were found to be seropositive for these viral infections; 23(1.28%) were HBV positive, 36(2.0%) were HCV positive, two (0.11%) were HIV positive and only one (0.06%) patient had both HBV and C. There was slight male preponderance (51.61%) in our study. Maximum seropositives (6.98%) were from the age group of 31-40 years, with decrease in incidence and increasing age. None of the patients were found in age group of less than 30 years. Conclusions: Preoperative screening of blood borne viral infections and following safe practice patterns plays vital role in identifying many asymptomatic carriers and minimizing transmission of virus from patients to health care workers and other patients. The high incidence of these infections in younger age group is a matter of concern suggesting these as an emerging new disease of young.